Assessment of the equivalence of a generic to a branded femoral stem. (March 2017) - Hothi, H.; Henckel, J.; Shearing, P.; Holme, T.; Cerquiglini, A.; Laura, A. Di; Atrey, A.; Skinner, J.; Hart, A.
Abstract : Aims: The aim of this study was to compare the design of the generic OptiStem XTR femoral stem with the established Exeter femoral stem. Materials and Methods: We obtained five boxed, as manufactured, implants of both designs at random (ten in total). Two examiners were blinded to the implant design and independently measured the mass, volume, trunnion surface topography, trunnion roughness, trunnion cone angle, Caput-Collum-Diaphyseal (CCD) angle, femoral offset, stem length, neck length, and the width and roughness of the polished stem shaft using peer-reviewed methods. We then compared the stems using these parameters. Results: We found that the OptiStems were lighter (p < 0.001), had a rougher trunnion surface (p < 0.001) with a greater spacing and depth of the machined threads (p < 0.001), had greater trunnion cone angles (p = 0.007), and a smaller radius at the top of the trunnion (p = 0.007). There was no difference in stem volume (p = 0.643), CCD angle (p = 0.788), offset (p = 0.993), neck length (p = 0.344), stem length (p = 0.808), shaft width (p = 0.058 to 0.720) or roughness of the polished surface (p = 0.536). Conclusion: This preliminary investigation found that whilst there were similarities between the two designs, the generic OptiStem is different to the branded Exeter design. Cite this article: Bone Joint J 2017;99-B:310–16.